Sampling - Thompson, Steven K., 1945- (Hoboken, N.J. : John Wiley & Sons, 2012)
"Sampling provides an up-to-date treatment of both classical and modern sampling design and estimation methods, along with sampling methods for rare, clustered, and hard-to-detect populations ... Organized into six sections, the book covers basic sampling, from simple random to unequal probability sampling; the use of auxiliary data with ratio and regression estimation; sufficient data, model, and design in practical sampling; useful designs such as stratified, cluster and systematic, multistage, double and network sampling; detectability methods for elusive populations; spatial sampling; and adaptive sampling designs."--Publisher.
Part 1: Basic sampling -- Simple random sampling -- Confidence intervals -- Sample size -- Estimating proportions, ratios, and subpopulation means -- Unequal probability sampling -- Part 2: Making the best use of survey data -- Auxiliary data and ratio estimation -- Regression estimation -- The sufficient statistic in sampling -- Design and model -- Part 3: Some useful designs -- Stratified sampling -- Cluster and systematic sampling -- Multistage designs -- Double or two-phase sampling -- Part 4: Methods for elusive and hard-to-detect populations -- Network sampling and link-tracing designs -- Detectability and sampling -- Line and point transects -- Capture-recapture sampling -- Line-intercept sampling -- Part 5: Spatial sampling -- Spatial prediction or Kriging -- Spatial designs -- Plot shapes and observational methods -- Part 6: Adaptive sampling -- Adaptive sampling designs -- Adaptive cluster sampling -- Systematic and strip adaptive cluster sampling -- Stratified adaptive cluster sampling.
Includes bibliographical references (pages 375-393) and indexes.
Print version record.
Keywords: Sampling (Statistics); MATHEMATICS -- Probability & Statistics -- General; Mathematics; MATHEMATICS -- Probability & Statistics -- General; Sampling (Statistics); Electronic books